1988
DOI: 10.1007/bf00201325
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-decay damage in minerals of the pyrochlore group

Abstract: Abstract. X-ray diffraction analysis and transmission electron microscopy have been used to study the effects of alpha-decay damage in pyrochlore group minerals, characterized by the general formula A1 ,~BzO6(O,OH,F)I -n'pH20.As defined by the XRD intensity ratio I/Io, both the saturation dose (for which I/Io =0.1-0.0) and the dose which signifies the initial loss of crystallinity (for which I/Io = 1.0-0.8) increase as a function of geologic age. The increase is attributed to annealing of isolated alpha-recoil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
84
1
4

Year Published

1994
1994
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(100 citation statements)
references
References 71 publications
11
84
1
4
Order By: Relevance
“…In the U-rich rim, the maximum dose was approximately 2*1017 alphas/mg, suggesting that ,most of the U-rich rim should be completely metarnict in the absence of annealing. This conclusion is based on previous studies which have shown that pyrochlore-group minerals become amorphous at a dose of > 10IG alphasdmg [6,12], and is in agreement with preliminary TEM and XRD results. Our TEM investigations revealed the presence of diffuse rings in electron difiaction images, and these rings could be due to radiation damage microstructure resulting from alpha recoil collisions.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In the U-rich rim, the maximum dose was approximately 2*1017 alphas/mg, suggesting that ,most of the U-rich rim should be completely metarnict in the absence of annealing. This conclusion is based on previous studies which have shown that pyrochlore-group minerals become amorphous at a dose of > 10IG alphasdmg [6,12], and is in agreement with preliminary TEM and XRD results. Our TEM investigations revealed the presence of diffuse rings in electron difiaction images, and these rings could be due to radiation damage microstructure resulting from alpha recoil collisions.…”
Section: Resultssupporting
confidence: 91%
“…5% crystallinity) in the studied rim sample (Fig. 4) is likely the result of partial annealing [12].…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Mainly Na, Ca, U, Th, Y, and REEs occupy the A-site, but also minor elements like Fe 2+ , Mn, Sn 2+ , Sb, Bi, Sr, Ba, Pb, K, and Cs have been found [16]. The B-site can be occupied by Nb, Ta, Ti, Fe 3+ , Zr, and Sn 4+ [16]. O can occupy the X-as well as the Y-site, whereas OH and F only occupy the latter [16].…”
Section: Introductionmentioning
confidence: 99%
“…Natural pyrochlore mineral samples have received extensive study, particularly by Lumpkin, Greegor, Ewing, and co-workers (GREEGOR, 1985a;1985b;LUMPKIN, 1980;1986d;1988a;1988b;1994;. Lumpkin and Ewing analyzed alpha-decay damage in pyrochlores having a wide range of chemical compositions, from 15 locations, with ages ranging up to 1.4 billion years.…”
Section: Consideration Of Individual Mineral Phasesmentioning
confidence: 99%